Penafsiran Ulang Konsep “Kontekstualisasi” dalam Hadis: Kajian atas Hadis Tentang Kepemimpinan Perempuan - Wendi Parwanto (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2022)
Claims that women are weak, not authoritative, and tend to use their feelings, make women discriminated against in the public sphere. Even in Islamic history, women are considered worthless so when a baby girl is born, it is considered a disgrace, and many are buried alive. Thus, in accordance with the times and knowledge, this paper will review the roles and gait of women, especially in their capacity as leaders. This paper will examine the text of the prophet's hadith about women's leadership and try to contextualize it with Indonesian reality. The conclusion of this article is that women are given things and obligations to become leaders as long as they have the capacity, capability, and quality to carry out their duties and responsibilities. So, in the context of 'worldly' leadership, it is not seen from gender, but from the qualifications, capabilities, and qualities possessed by a person.